2005
DOI: 10.1002/ldr.644
|View full text |Cite
|
Sign up to set email alerts
|

Soil carbon sequestration in sub-Saharan Africa: a review

Abstract: Restoration of degraded soils is a development strategy to reduce desertification, soil erosion and environmental degradation, and alleviate chronic food shortages with great potential in sub-Saharan Africa (SSA). Further, it has the potential to provide terrestrial sinks of carbon (C) and reduce the rate of enrichment of atmospheric CO 2 . Soil organic carbon (SOC) contents decrease by 0 to 63 per cent following deforestation. There exists a high potential for increasing SOC through establishment of natural o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
123
4
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(134 citation statements)
references
References 83 publications
(82 reference statements)
6
123
4
1
Order By: Relevance
“…Schultz (1988) showed that C and N declined by 6% with burning but increased by 1% with stubble retention. Vagen et al (2005) concluded that the largest potential for increasing SOC is through the establishment of natural or improved fallow systems (agroforestry) with attainable C accumulation rates from 0.1 to 5.3 Mg C ha K1 yr…”
Section: Conservation Agriculture Definedmentioning
confidence: 99%
“…Schultz (1988) showed that C and N declined by 6% with burning but increased by 1% with stubble retention. Vagen et al (2005) concluded that the largest potential for increasing SOC is through the establishment of natural or improved fallow systems (agroforestry) with attainable C accumulation rates from 0.1 to 5.3 Mg C ha K1 yr…”
Section: Conservation Agriculture Definedmentioning
confidence: 99%
“…Yet, the impacts of land-use change on SOC dynamics in sub-Saharan African ecosystems are still understudied, especially across diverse landscapes. Meta-analyses have shown that the conversion of forest/natural vegetation to agriculture leads to an overall loss of SOC (Post and Mann 1990;Schlesinger 1997;Ogle et al 2005;Vågen et al 2005;Don et al 2011), which has resulted in renewed efforts for restoring OC in agricultural soils (Lal et al 2004;Lal 2007;Tittonell and Giller 2013;Vanlauwe et al 2014). However, systematic surveys are needed to understand spatial variability of soil health indicators across the landscape, including interactions between inherent soil properties, SOC dynamics and land use, that enable targeted interventions at the plot and landscape-scales.…”
Section: Introductionmentioning
confidence: 99%
“…Subsistence farming in subSaharan Africa, in general, is, thus, characterized by low external input, low crop yield, food insecurity, nutrient mining and environmental degradation (Stoorvogel et al, 1993;Rhodes, 1995;Mafongoya et al, 2006). Strategies must, therefore, be developed to restore soil fertility, to reduce erosion and environmental degradation in order to increase food production and alleviate chronic hunger in the zone (Vagen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%